Urgensi Pelindungan Ekspresi Budaya Tradisional Seni Genggong Sumedang Sebagai Objek Kekayaan Intelektual Komunal Di Indonesia - Khofiyanisa, Nurauliya Syifa; Miranda Risang Ayu Palar; Laina Rafianti (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
The protection of traditional cultural expressions within the concept of Communal Intellectual Property is an effort to preserve cultural aspects. One such expression needing protection is the Genggong Art of Sumedang. This research aims to understand the issues related to the Genggong Art of Sumedang, which has not yet received defensive protection as a Communal Intellectual Property object, and the legal provisions that can support its protection. Using a normative juridical and sociological juridical approach, the research collects primary data through field studies and interviews, and secondary data through literature studies, including relevant regulations and other secondary legal materials. The findings indicate that normative provisions on intellectual property in Indonesia have not been optimally implemented. This is due to a lack of socialization about the importance of communal intellectual property protection and an understanding of registration procedures. Therefore, optimal cooperation and coordination are needed both in the registration context between the originating community and the Sumedang Regency Government, as well as in promoting the importance of defensive protection of traditional cultural expressions between the Sumedang Regency Government and the Ministry of Law and Human Rights.